Potrait Fotografi Kehidupan Ma Ayu - Shauma Silmi Faza; Andang Iskandar; Ismet Ruchimat (PANTUN, 2022)
ABSTRACTThe reality of Ma Ayu's life has become the trace of memory saved in the system of sensory memory. The information about Ma Ayu's life journey is divided into three dimensions, namely adolescence, productive period, and survival period. Ma Ayu's story stimulates to play a role of humans as homo narrans, namely the representation of individuals as the subject of the story through the medium of photography. This work is presented in the category of ethical photographs summarized in a series of documentary photos and essays so that they contain photos which can be evaluated ethically. The method applied to reveal Ma Ayu's figure is by using a humanitarian approach for social documentary. This work produces two findings, the first is the perspective of Ma Ayu's personal identity as a representation of Javanese woman who struggle in the social complexities of different cultures. The second is to produce visual aesthetic products in the form of photography showing Ma Ayu's characteristics as a hardworking, high-spirited, and independent woman.Keywords: Biography, Humanitarian, Visual AestheticABSTRAKRealitas kehidupan Ma Ayu telah menjadi jejak memori yang tersimpan dalam sistem ingatan sensorik. Informasi mengenai perjalanan hidup Ma Ayu terbagi menjadi tiga dimensi, yaitu masa remaja, masa produktif, dan masa survive. Kisah Ma Ayu menjadi stimulus untuk memainkan peran manusia sebagai homo narrans, yaitu keterwakilan individu sebagai subjek cerita melalui medium fotografi. Karya ini disajikan melalui kategori foto etik (ethically photographs), yang dirangkum dalam rangkaian foto dokumenter dan esai sehingga memuat foto-foto yang dapat dinilai secara etik. Adapun metode yang digunakan untuk membedah figur Ma Ayu yaitu dengan menggunakan pendekatan kemanusiaan (humanitarian approach for social documentary). Karya ini menghasilkan dua temuan, pertama berupa perspektif identitas personal Ma Ayu sebagai representasi perempuan Jawa yang berjuang dalam kompleksitas sosial yang berbeda kultur. Kedua menghasilkan produk estetika visual dalam bentuk fotografi yang menunjukkan karakteristik Ma Ayu dengan sifat pekerja keras, semangat yang tinggi, dan mandiri.Kata Kunci : Biografi, Humanitarian, Estetika Visual.